The Role of Social Media Narratives in Juvenile Bullying Prevention within Indonesian and German Legal-Psychological Contexts - Lingga, Sifollia Putri; Sapni, Dripsy Teresa Pugon; Han, Hubert Putra (Universitas Negeri Semarang, 2025)
Juvenile violence and bullying in Indonesia continue to rise despite the presence of a normative restorative framework under the Juvenile Criminal Justice System Act (UU SPPA) and educational regulations intended to prevent school-based violence. This study examines how preventive efforts can be strengthened through an integrated legal, psychological, and digital-media approach by comparing Indonesia’s system with Germany’s welfare-oriented model under the Jugendgerichtsgesetz (JGG) and Sozialgesetzbuch VIII (SGB VIII). Using a normative juridical method and comparative analysis, the research finds that Indonesia’s diversion practices remain largely procedural, lacking the professional facilitation, victim support, and psychological engagement necessary for genuine restorative outcomes. By contrast, Germany embeds offender victim mediation within a multidisciplinary welfare ecosystem, supported by structured emotional-literacy programs and digital-behavior education. The study also highlights the emerging role of social media in shaping youth behavior and public narratives about juvenile justice, offering both risks and opportunities for prevention. The findings suggest that Indonesia’s preventive strategies would benefit from professionalizing restorative facilitation, expanding psychological services, integrating digital-literacy and online-empathy curricula, and collaborating with social-media platforms to promote prosocial and restorative content. These measures would align Indonesia’s juvenile justice system with contemporary youth realities and reinforce long-term violence prevention.